2006
DOI: 10.1248/cpb.54.103
|View full text |Cite
|
Sign up to set email alerts
|

Chymotrypsin Inhibitory Triterpenoids from Silybum marianum

Abstract: Silybum marianum GAERTH is an erect stout biennial, herb belonging to the family Compositae which comprises about 1000 genera and 20000 species. S. marianum is common in Kashmir at an altitude of 1800-4000 m and is cultivated for ornaments in gardens. The plant is used in the treatment of hepatitis, cirrhosis, regeneration from liver diseases, and liver poisoning.1) A decoction of this plant is also used by the local physicians for the treatment of a variety of viral diseases.1) A literature survey revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The relative configuration of 1 was determined by the 1 H-NMR ( Table 1 ) and NOESY data. 1 H-NMR chemical shift of CH 3 -21 (δ H 0.94, d, J = 6.6 Hz) confirmed that compound 1 was classified as the tirucallane series [ 11 , 12 , 13 ]. The large coupling constants H-C(3) (δ H 3.31, J = 9.5, 6.4 Hz) obviously indicated that the 3-OH group was in equatorial β-position [ 10 , 14 ].…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The relative configuration of 1 was determined by the 1 H-NMR ( Table 1 ) and NOESY data. 1 H-NMR chemical shift of CH 3 -21 (δ H 0.94, d, J = 6.6 Hz) confirmed that compound 1 was classified as the tirucallane series [ 11 , 12 , 13 ]. The large coupling constants H-C(3) (δ H 3.31, J = 9.5, 6.4 Hz) obviously indicated that the 3-OH group was in equatorial β-position [ 10 , 14 ].…”
Section: Resultsmentioning
confidence: 85%
“…The comparison of 1 H-NMR, 13 C-NMR ( Table 1 and Table 2 ) and NOESY data ( Figure 2 ) showed that compound 2 and the known Compound 1 [ 10 ] were semblable in structure, except that a Hydrogen at C-11 of Compound 1 was superseded by a hydroxyl group in compound 2 , which was proven by correlations of H-11 (δ H 4.69, t, J = 8.2 Hz) with C-8 (δ C 140.44), C-9 (δ C 161.30) and C-12 (δ C 42.83) in HMBC spectrum ( Figure 3 ). The large coupling constants H-C(3) (δ H 3.31, J = 9.5, 6.4 Hz) obviously indicated that the 3-OH group was in equatorial β-position [ 11 , 12 ]. The NOESY correlations ( Figure 2 ) H-C(3) (δ H 3.31)/H-C(5) (δ H 1.62–1.68), H-C(3) (δ H 3.31)/CH 3 -28 (δ H 1.01), H-C(11) (δ H 4.69)/CH 3 -18 (δ H 0.73), CH 3 -30 (δ H 1.16)/H-C(17) (δ H 1.55–1.60), CH 3 -29 (δ H 0.93)/CH 3 -19 (δ H 1.27), CH 3 -18 (δ H 0.73)/CH 3 -19 (δ H 1.27), showed that H-C(3), H-C(5), H-C(17), and CH 3 -28 were all in α -orientation, whereas 11-OH, CH 3 -19, CH 3 -30 and CH 3 -29 were in β-orientation, and no correlations between CH 3 -21/CH 3 -18 [ 10 , 15 ] indicated that it belonged to the euphane-type triterpenes.…”
Section: Resultsmentioning
confidence: 99%
“…All 12 of the known compounds (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) were identified according to the spectroscopic data ( 1 H-NMR, 13 7) [4], kansenone (8) [10], epi-kansenone (9) [10], kansuinin A (10) [4,17], kansuinin D (11) [4], kansuinin E (12) [4], euphol (13) [4,18], and tirucallol (14) [4,19].…”
Section: Resultsmentioning
confidence: 99%
“…The comparison of 1 H-NMR, 13 C-NMR (Tables 1 and 2) and NOESY data (Figure 2) showed that compound 2 and the known Compound 1 [10] were semblable in structure, except that a Hydrogen at C-11 of Compound 1 was superseded by a hydroxyl group in compound 2, which was proven by correlations of H-11 (δ H 4.69, t, J = 8.2 Hz) with C-8 (δ C 140.44), C-9 (δ C 161.30) and C-12 (δ C 42.83) in HMBC spectrum (Figure 3). The large coupling constants H-C(3) (δ H 3.31, J = 9.5, 6.4 Hz) obviously indicated that the 3-OH group was in equatorial β-position [11,12]. The NOESY correlations (Figure 2 17), and CH 3 -28 were all in α-orientation, whereas 11-OH, CH 3 -19, CH 3 -30 and CH 3 -29 were in β-orientation, and no correlations between CH 3 -21/CH 3 -18 [10,15] indicated that it belonged to the euphane-type triterpenes.…”
Section: Resultsmentioning
confidence: 99%
“…The large coupling constant (J ¼ 11.0 Hz) between HÀC(3) and H b ÀC(2) clearly indicated that the 3-OH group was in equatorial b-position [7]. The NOESY correlations ( showed that 1 and 2 were very closely related to each other, including configuration, except for the monounsaturated side-chain moiety.…”
mentioning
confidence: 96%